1993
DOI: 10.1002/mrm.1910290403
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of lung cancers by the use of 1H nuclear magnetic resonance spectroscopy of tissue extracts and discriminant factor analysis

Abstract: Using proton magnetic resonance spectroscopy (1H MRS) spectra were obtained in vitro from extracts of four types of lung cancer (squamous cell, adenocarcinoma, large cell, small cell) and normal lung. The hydrophilic phase of the chloroform/methanol-water extracts yielded several distinct peaks. Among them the peak areas for cholines, creatines, glycine, and alanine, and their ratios were calculated and used as parameters to characterize different lung tissues. The ratios, cholines/alanine and glycine/alanine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Thus 17 samples were prepared and a total of 33 spectra were included in the PCA of the correlation matrix. The size of the final dataset is comparable to the reported pattern-recognition studies of NMR metabolomics data (32,33,49). Error analysis suggests that only the first eigenvalue is clearly distinct, corresponding to one significant PC.…”
Section: Resultsmentioning
confidence: 68%
“…Thus 17 samples were prepared and a total of 33 spectra were included in the PCA of the correlation matrix. The size of the final dataset is comparable to the reported pattern-recognition studies of NMR metabolomics data (32,33,49). Error analysis suggests that only the first eigenvalue is clearly distinct, corresponding to one significant PC.…”
Section: Resultsmentioning
confidence: 68%
“…Few studies have focused on 1 H-MRS of lung cancer. However, in a study comparing different types of lung cancer and normal lung, Hanaoka et al (13) found significantly different values in the ratios of Cr/ glycine and Cr/Cho among almost all types. Cr/glycine, Cr/Cho, and Cr/alanin ratios are higher in squamous cell carcinoma than in normal lung.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, only in vitro MRS studies have been conducted on lung tissue. Hanaoka et al (13) reported that Lac in lung tissue increased rapidly after surgical disruption. However, since it has not been possible to standardize experimental conditions to accurately quantify Lac, it is difficult to measure the amount of Lac in lung cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction was performed according to Folch et al 9 This method was designed originally for the extraction of hydrophobic substances, but later also found to be useful for extracting the low molecular weight hydrophilic organic compounds essentially without any in vitro modifications, such as oxidation and hydrolysis. [10][11][12] Liver tissue (4.0-5.0 g wet wt) was homogenized with 20-fold volume of chloroform-methanol (2:1), and then the homogenate was filtered. A five-fold volume of H 2 O was added to the filtrates and allowed to stand for about 24 h at 4ЊC.…”
Section: Rat Model For Liver Ischemia/reperfusionmentioning
confidence: 99%